Risk Factor Analysis of Low Back Pain in Employees of Drinking Water Store in Medan Selayang Sub-District - Andri Josua Barutu; Heru Rahmadhany (Sumatera Medical Journal, 2022)
Background. Low back pain is defined as feeling of pain and discomfort in the area between the costal margin and inferior gluteal fold, with or without radiating pain. In Indonesia, LBP was fifth ranks in term of disability-adjusted life years (DALYs). Aim. This study aims to determine risk factors for LBP in employees of drinking water store in Medan Selayang sub-District, Medan. Method. This research is an observational analytic study with cross-sectional design. This study used consecutive sampling method. Minimum sample size in this study was 97 samples. Subjects in this study were employees of drinking water store in Medan Selayang sub-District. Data used in this study was primary data from samples through filling out questionnaires. Analysis used in this study was univariate analysis, bivariate with chi-square, and multivariate with logistic regression. Result. From 100 samples, 39 respondents (39%) experienced LBP. Based on bivariate analisis, p value ≤ 0.05 was found for age, body mass index, and duration of work. P value ≥ 0.05 was obtained for years of work and lifting frequency. Based on multivariate analysis with regression logistic, p value ≤ 0.05 was obtained for body mass index (p = 0.089) and work duration (p = 0.011) which indicated that work duration was the most dominant risk factor. Conclusion. There’s a relationship between age, body mass index, and work duration with the work duration being the most dominant risk factor for the incidence of low back pain in water gallon worker. .